2011
DOI: 10.1007/s10584-011-0045-5
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of observed climate change adaptation in developed nations

Abstract: We develop and apply a systematic mixed-methods literature review methodology to identify and characterize how climate change adaptation is taking place in developed nations. We find limited evidence of adaptation action. Where interventions are being implemented and reported on, they are typically in sectors that are sensitive to climate impacts, are most common at the municipal level, facilitated by higher-level government interventions, with responses typically institutional in nature. There is negligible d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
229
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 381 publications
(239 citation statements)
references
References 16 publications
8
229
0
2
Order By: Relevance
“…Adaptation research in developed nations has largely prioritised broader socio-spatial scales, positioning government and institutional stakeholders (not households) as key adaptive actors. A systematic review of climate change adaptation research in developed nations found few articles documenting household-scale adaptation (Ford et al 2011). Those studies that did focus on households mostly considered direct climatic stimuli and impacts, such as heatwaves (Wolf et al 2010;Saman et al 2013), flooding and sea-level rise (Harvatt et al 2011;Barnett et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Adaptation research in developed nations has largely prioritised broader socio-spatial scales, positioning government and institutional stakeholders (not households) as key adaptive actors. A systematic review of climate change adaptation research in developed nations found few articles documenting household-scale adaptation (Ford et al 2011). Those studies that did focus on households mostly considered direct climatic stimuli and impacts, such as heatwaves (Wolf et al 2010;Saman et al 2013), flooding and sea-level rise (Harvatt et al 2011;Barnett et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the mandate of local government is expanding, due to the shifting of responsibility from higher levels of authority to lower levels of authority, particularly from state and provincial authorities (Ivey et al 2004). Such constraints to action may explain why the apparent interest in adaptation and adaptation planning hasn't necessarily translated into the implementation of actions to reduce vulnerability (Repetto 2008;Ford et al 2011;Berrang-Ford et al 2011;Preston et al 2011).…”
mentioning
confidence: 99%
“…The research methodology uses a systematic literature review, which involves reviewing documents according to clearly formulated criteria, using systematic and explicit methods to select and critically appraise relevant information (Lesnikowski et al 2011;Berrang-Ford et al 2011;Ford et al 2010). This approach, common in health sciences, has recently been applied to climate change studies to assess current knowledge about climate change impacts and adaptation measures and relies on peer-reviewed literature and national adaptation planning documents focused on water (Plummer et al 2012), human health (Lesnikowski et al 2011(Lesnikowski et al , 2013, the Arctic regions of Canada (Ford and Pearce 2010), within climate change hotspot regions (see articles in this special edition), and in general, regarding the governance of adaptation (Biesbroek et al 2014).…”
Section: Methodsmentioning
confidence: 99%